A highly hydrophilic cation exchange nonwoven with a further modifiable epoxy group prepared by radiation-induced graft polymerization. Issue 40 (29th September 2021) - Pan, Xiao-han; Zu, Jian-hua
Abstract : Novel cation exchange nonwoven PP- g -SSS/GMA containing epoxy and sulfonic groups was successfully prepared via radiation-induced simultaneous grafting polymerization by attaching GMA and SSS monomers onto PP nonwoven. Abstract : Novel cation exchange nonwoven PP- g -SSS/GMA containing epoxy and sulfonic groups was successfully prepared via radiation-induced simultaneous grafting polymerization by attaching glycidyl methacrylate (GMA) and styrene sulfonic sodium (SSS) monomers onto nonwoven polypropylene (PP). The ion exchange capacity of the obtained PP- g -SSS/GMA reached more than 1.5 mmol g −1 and the content of the epoxy groups with potential modifiable properties was above 3 mmol g −1 . The relative content of the two functional groups could be adjusted via changing the initial monomer concentration ratio. Scanning electron microscope (SEM) images showed that the polymer surface was fully covered with grafts after modification and those amorphous grafts diluted the crystallinity of the matrix, as revealed via differential scanning calorimetry (DSC). Attenuated total reflection spectroscopy (ATR) confirmed the successful grafting of GMA and SSS onto PP nonwovens. Water contact angle measurements showed that the contact angle decreased from 100.94° for the PP matrix to 0° for PP- g -SSS/GMA with a 56% degree of grafting, indicating the outstanding hydrophilicity of PP- g -SSS/GMA upon the introduction of SSS. Besides this, the epoxy groups on PP- g -SSS/GMA could be further modified via reacting them with chemical compounds with selective adsorption groups. Ag(i ) adsorption tests proved that PP- g -SSS/GMA@EDA obtained via the ethanediamine (EDA) modification of epoxy groups on PP- g -SSS/GMA shows excellent selectivity towards Ag(i ), and the hydrophilicity brought about by sulfonic groups also ensured a fast adsorption rate. The novel cation exchange nonwoven PP- g -SSS/GMA fabric has potential applications in water treatment, as its strong hydrophilicity could speed up the diffusion rates of adsorbed ions, and further functionalization of the epoxy groups could enable it to selectively adsorb ions in aqueous solutions.